Pengaruh Teknik Pernafasan Senam Tera terhadap Pengurangan Nyeri Kala I Persalinan - Ryka Juaeriah; Yuliana; Anissa, Gemilang Rahma; Sabna Tiara Azzahra; Zulfa Husna Maab (Sultan Agung Islamic University of Semarang, 2024)
The majority of delivering mothers experience pain during the first stage of childbirth (Stage I). The intensity of pain varies depending on the progress of cervical dilation. Pain management during childbirth is a specific concern for the well-being of both the mother and the fetus. Various pharmacological and non-pharmacological methods have been implemented to alleviate labor pain. Tera exercises, traditionally associated with physical activities for the elderly, have now evolved into Tera exercises incorporating breathing techniques for mothers in Stage I of labor. The aim of this research is to determine the impact of Tera breathing techniques on reducing pain during Stage I of labor for delivering mothers.The research design employed a quasi-experimental approach with a pretest-posttest without a control group design. Mothers in Stage I of labor underwent pretest-posttest assessments using the Numeric Rating Scale (NRS) to measure pain intensity. Twenty-two samples received intervention in the form of breathing techniques from Tera exercises. The results of the study indicate that the application of Tera breathing techniques significantly contributes to the reduction of labor pain during Stage I. Before the intervention, out of 22 respondents, 15 experienced moderate pain, 5 had severe pain, and 2 reported mild pain. After the intervention, there was a decrease, with 13 experiencing moderate pain, 9 reporting mild pain, and none feeling severe pain. The Tera breathing technique effectively reduces pain levels during Stage I of labor. Keywords: Labor Pain, Breathing, Tera Gymnastics